Secure student attendance system based on geo-location and QR code technologies - Noor Fathin Shahirah, Ahmat (2018)
Secure Student Attendance System Based On Geo-Location and QR Code Technologies is a system that facilitates lecturers to take attendance of the students more systematic and easy to use. This system is created to improve current student attendance system which uses manual sign attendance sheets. For example, many lecturers in Universiti Malaysia Pahang still use manual method to take attendance of the system, the lecturer need to call name of the students one by one before starting the learning session. This method usually takes about 10 to 15 minutes before the learning session can take place. Hence, this QR code-based system is considered as an alternative to overcome this time consuming problem. Lecturers only need to place a QR Code on the presentation slide for the students scan it using this system through their own smartphone. Additionally, there are several cases where students sign the attendance on behalf of their friends who are absent on that class. This case happens when the lecturers distribute the attendance sheets to the class during learning session. To reduce this unethical practice, the proposed system provides a location tracking function where the QR code is scanned. This function is created to prevent students from cheating their presence in the classroom. This system uses smartphones as the main field because smartphones have been regarded as an ideal for every student. Majority students nowadays have their smartphone so this system is easier to use by them. As a conclusion, this system has been through testing process among students and lecturers of Universiti Malaysia Pahang.